3D graphene-based adsorbents: Synthesis, proportional analysis and potential applications in oil elimination - Wong, L.Y. (Elsevier Ltd, 2022)
The suitability and efficacy of three-dimensional (3D) graphene, including its derivatives, have garnered widespread attention towards the development of novel, sustainable materials with ecological amenability. This is especially relevant towards its utilization as adsorbents of wastewater contaminants, such as heavy metals, dyes, and oil, which could be majorly attributed to its noteworthy physicochemical features, particularly elevated chemical and mechanical robustness, advanced permeability, as well as large specific surface area. In this review, we emphasize on the adsorptive elimination of oil particles from contaminated water. Specifically, we assess and collate recent literature on the conceptualization and designing stages of 3D graphene-based adsorbents (3DGBAs) towards oil adsorption, including their applications in either batch or continuous modes. In addition, we analytically evaluate the adsorption mechanism, including sorption sites, physical properties, surface chemistry of 3DGBA and interactions between the adsorbent and adsorbate involving the adsorptive removal of oil, as well as numerous effects of adsorption conditions on the adsorption performance, i.e. pH, temperature, initial concentration of oil contaminants and adsorbent dosage. Furthermore, we focus on the equilibrium isotherms and kinetic studies, in order to comprehend the oil elimination procedures. Lastly, we designate encouraging avenues and recommendations for a perpetual research thrust, and outline the associated future prospects and perspectives. Â© 2021 Elsevier Ltd